The Control of The Kadi and The Muhtesib on The Urban Guilds in The Ottoman Empire - Mohammad Hefni (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2017)
Success of the Ottoman empire as one of the greatest, most extensive, and longest-lasting empires in the history of the world could not be released from the efforts of the government to organize the state throught establishment various institutions. Among them are judicials instititution such as kadi courts and Hisbah institutions which was led by a muhtesib. Therefore, this paper discusses the relationship and the interaction between the kadi and the muhtesib in the Ottoman empire, and their historical roots in the periods before. The position of a kadi and a muhesib has existed in periods before the Ottoman empire. A kadi has existed since the Prophet Muhammad pbuh period. While, a muhtesib historically has began in the Greco-Roman agoranomos. In the Ottoman empire, both became important governmental functions. They had the power to pronounce decisions on everything connected with the sharî'a and the Sultanic law. They played roles in controlling urban life, its economic activities in particular. All the production and manufacturing activities in the cities that were carried out within the framework of the guild organization was under the control of the kadi and the muhtesib. For example a craft guilds and a creditor guilds.